FEATURES OF THE HERO’S IDENTIFICATION IN V. PELEVIN’S NOVEL IPHUCK 10 - Agata Osipova (Bright Mind Publishing, 2026)
The article is devoted to the analysis of the transformation of the image of the “new” hero in 21st-century Russian literature in the context of marginality and existential search. It examines the shift from the classical understanding of marginality as a form of social or cultural exclusion to its interpretation as an ontological condition that shapes contemporary subjectivity. Special attention is paid to the reduction of existential experience and the transformation of forms of meaning-making within posthumanist culture, where traditional categories such as choice, responsibility, and authenticity lose their former significance. Drawing on material from contemporary prose, the study identifies the main types of the marginal hero and analyzes the ways in which the existential question is represented under conditions of simulation and the functionalization of the subject. The conclusion argues that marginality becomes a normative mode of existence for the “new” hero, while existential search functions as a means of registering the crisis of existence as the foundation of human experience.
Keywords: Existentialism, postmodernism, contemporary Russian literature, identity, philosophical reflection, literary process.